Special nuclear layer contacts between starburst amacrine cells in the mouse retina - Mu, Shang; Turner, Nicholas L.; Silversmith, William M.; Jordan, Chris S.; Kemnitz, Nico; Sorek, Marissa; David, Celia; Jones, Devon L.; Bland, Doug; Moore, Merlin; Sterling, Amy Robinson; Seung, H. Sebastian (Frontiers in Ophthalmology, 2023)
Starburst amacrine cells are a prominent neuron type in the mammalian retina that has been well-studied for its role in direction-selective information processing. One specific property of these cells is that their dendrites tightly stratify at specific depths within the inner plexiform layer (IPL), which, together with their unique expression of choline acetyltransferase (ChAT), has made them the most common depth marker for studying other retinal neurons in the IPL. This stratifying property makes it unexpected that they could routinely have dendrites reaching into the nuclear layer or that they could have somatic contact specializations, which is exactly what we have found in this study. Specifically, an electron microscopic image volume of sufficient size from a mouse retina provided us with the opportunity to anatomically observe both microscopic details and collective patterns, and our detailed cell reconstructions revealed interesting cell-cell contacts between starburst amacrine neurons. The contact characteristics differ between the respective On and Off starburst amacrine subpopulations, but both occur within the soma layers, as opposed to their regular contact laminae within the inner plexiform layer.